The Influence of Competence and Work Culture on the Performance of Elementary School Teachers Inpres 03 Tatura Palu - Revita, Meri; Surayya, Surayya; Sari, Dyah Fitria Kartika; Lele, Aco (SEAN Institute, 2024)
This research was conducted at SD Inpres 03 Tatura Palu with the aim of the research to determine the influence of competence and work culture on teacher performance at SD Inpres 03 Tatura Palu. Teachers as one of the implementers of education in schools are an important factor in achieve success in quality education. Teachers in producing their performance cannot be separated from the competencies they have and the work culture applied in an educational institution. Therefore, competency and work culture will affect teacher performance. The results of this study are the influence of competence and work culture on teacher performance.